Semantic Diversity for the formula of the name of subject Reading in the models of the Quran - Yayai, Malek; Mousa, Samera; Kassem, Bushra (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
- This research comprised "The present participle" in the Holy Quran statistically, syntactically and semantically. - "The present participle" where from concept, function and addition. And this section concentrated on variances between kufices and addition. - The study of the most important syntactical sides, which deal with the present participle in the Holy Quran. This section was attached with statistical tables clarifying the present participle's function, addition and parsing in the Holy Quran.